2008
DOI: 10.1345/aph.1l123
|View full text |Cite
|
Sign up to set email alerts
|

Medication Reconciliation Effect on Prolonged Inpatient Stress Ulcer Prophylaxis

Abstract: The strategy of MR alone will not decrease the incidence of prolonged SUP in hospitalized patients. Other techniques should be evaluated to encourage appropriate use of acid-suppressive agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(65 citation statements)
references
References 19 publications
0
65
0
Order By: Relevance
“…In none of the studies was the allocation sequence randomly assigned and the allocation concealed. Six studies did not report similar baseline characteristics [ 40 , 42 , 43 , 48 50 ], eight studies did not perform a sample size calculation [ 40 42 , 44 , 45 , 48 50 ], and nine studies had no plan for handling missing data [ 40 , 42 46 , 48 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…In none of the studies was the allocation sequence randomly assigned and the allocation concealed. Six studies did not report similar baseline characteristics [ 40 , 42 , 43 , 48 50 ], eight studies did not perform a sample size calculation [ 40 42 , 44 , 45 , 48 50 ], and nine studies had no plan for handling missing data [ 40 , 42 46 , 48 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other studies showed the positive impact of pharmacists in improving clinical and cost outcomes in hospitalized patients receiving PPI by either switching patients to a less expensive agent or discontinuing the medication for unnecessary indication. Type of interventions included direct collaboration with physicians, guidelines implementation, or pharmacist-led medication reconciliation [8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…3 Second, there is the belief that the risk for an adverse event is low given the short time therapy is administered, but many patients get discharged to home on stress ulcer prophylaxis. 4 Consequently, inadvertent long-term use could lead to adverse events (see the accompanying article by Abrahamsen et al 5 ) and added cost. Finally, there is the misbelief of what truly constitutes "risk" for stressrelated clinically significant bleeding.…”
Section: Acid Suppressive Therapy In Noncritically Ill Patientsmentioning
confidence: 99%